2021
DOI: 10.2166/hydro.2021.056
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of ecohydrological processes influencing water supplies in the Tuul River watershed of Mongolia

Abstract: Achieving sufficient water supplies for multiple uses in the watershed is a major public policy issue. Understanding the current ecohydrologic processes is essential to assess potential impacts on hydrologic regimes. The Tuul River (TR) watershed faces a cold, continental climate with water supply variability. This study aims to simulate watershed processes in the TR watershed and subbasins and analyze the influences of those processes on water resources. Watershed hydrologic processes and their impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…City profile Ulaanbaatar is Mongolia's capital city. The population of Ulaanbaatar is around 1.6 million [28] which represents nearly 50% of the country's total population [29]. Due to its high altitude (about 1,350 metres above sea level) and continental location, Ulaanbaatar experiences extreme seasonal variations in temperature.…”
Section: 1mentioning
confidence: 99%
“…City profile Ulaanbaatar is Mongolia's capital city. The population of Ulaanbaatar is around 1.6 million [28] which represents nearly 50% of the country's total population [29]. Due to its high altitude (about 1,350 metres above sea level) and continental location, Ulaanbaatar experiences extreme seasonal variations in temperature.…”
Section: 1mentioning
confidence: 99%
“…Studies have been conducted to estimate water resources using the long-term discharge data and flow measurements, as well as, some specific models, such as SWAT, RIBASIM, HBV, and HEC-Geo HMS in the Tuul River basin. For instance, in recent years many national hydrologists tried to apply Soil Water Assessment Tool (SWAT) in simulating ecohydrological process and climate change impact in the Tuul River basin [6]- [8]. They concluded that the hydrological model has performed well in simulating hydrological processes in watersheds and emphasized that data availability, monitoring information for the calibration and validation of the simulation model, were major limitations of those research works.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…The year to year fluctuations in rainfall as well as the fluctuations within the monsoon season governs the crop growth its development and yield potential [9,10]. Even in monsoon months also crops are subjected to moisture stress due to occasional dry spells [11,12]. The rainfall distribution is erratic making the crop vulnerable to abiotic stress beyond management level even during monsoon.…”
Section: Introductionmentioning
confidence: 99%